The third space of sovereignty : the postcolonial politics of U.S.-indigenous relations - Bruyneel, Kevin (Minneapolis : University of Minnesota Press, 2007)
The Third Space of Sovereignty offers fresh insights on such topics as the end of treaty-making in 1871, U.S. citizenship in the 1920s, native politics during the civil rights era, and the current issues surrounding casinos. Kevin Bruyneel shows how native political actors have effectively contested the limits that the United States has imposed on their ability to develop economically and politically on their own terms.
Introduction: Politics on the boundaries -- The U.S.-indigenous relationship : a struggle over colonial rule -- Resisting American domestication : the U.S. Civil War and the Cherokee struggle to be "still, a nation" -- 1871 and the turn to postcolonial time in U.S.-indigenous relations -- Indigenous politics and the "gift" of U.S. citizenship in the early twentieth century -- Between civil rights and decolonization : the claim for postcolonial nationhood -- Indigenous sovereignty versus colonial time at the turn of the twenty-first century -- Conclusion: The third space of sovereignty.
Includes bibliographical references (pages 271-290) and index.
Print version record.
JSTOR
Keywords: Indians of North America -- Politics and government; Indians of North America -- Government relations; Indians of North America -- Civil rights; Self-determination, National -- United States; Postcolonialism -- United States; United States -- Race relations; United States -- Politics and government; Droit des peuples à disposer d'eux-mêmes -- États-Unis.; Postcolonialisme -- États-Unis.; États-Unis -- Relations raciales; États-Unis -- Politique et gouvernement; Peuples autochtones -- États-Unis -- Relations avec l'État.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies; Indians of North America -- Civil rights; Indians of North America -- Government relations; Indians of North America -- Politics and government; Politics and government; Postcolonialism; Race relations; Self-determination, National; United States; Electronic books